Convolutions of generalized measures - Padvelskis, Kazimieras; Bikelis, Algimantas (Lietuvos matematikos rinkinys, 2009)
The convolutions of probability distributions of independent random variables are analysed in this paper.
Keywords: compound Poisson distribution; Bergström’s identity; Grigelionis’ asymtotic expansion